The Future of Leadership: Transforming HR Management through Adaptive Leadership Models - Siham Farhat Hasan; Amhmmed Mohammed Eisay (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
This research paper explores the role of adaptive leadership in transforming HR management, highlighting its impact on employee engagement, talent retention, and organizational culture. As organizations face an increasingly complex and uncertain environment, traditional leadership models are proving inadequate, necessitating a shift towards more flexible, responsive, and collaborative approaches. Through a comprehensive analysis of adaptive leadership practices, this study reveals how HR leaders can navigate challenges, foster inclusivity, and drive innovation within their teams. The findings demonstrate that adaptive leadership enables HR professionals to respond effectively to change, leverage technology, and create a culture of continuous learning, ultimately enhancing organizational resilience and success. While challenges such as resistance to change and ambiguity exist, the paper offers practical recommendations for implementing adaptive leadership and developing training programs that prepare HR leaders for the complexities of the modern business landscape.